Influence of COVID-19 on air travel - A scenario study toward future trusted aviation. (January 2023) - Michelmann, Johannes; Schmalz, Ulrike; Becker, Axel; Stroh, Florian; Behnke, Sebastian; Hornung, Mirko
Abstract: This paper develops three scenarios for the aviation industry's recovery from COVID-19 until 2030 by utilizing the scenario methodology. Besides the short- and mid-term pandemic development, the study takes into account the industry's adaptation to changes in the market environment, e.g., toward sustainability and hygiene requirements. The resulting scenarios include the expected point in time of full air traffic recovery to pre-crisis levels. Subsequent implications suggest that most COVID-19-related hygiene measures along the travel chain disappear after the pandemic is contained. Some measures might serve as a differentiator between airline business models, while others are expected to become a new standard. Implications for environmental awareness and resulting operational and technical measures include changes in society's attitude toward traveling post-pandemic, especially in light of varying levels of environmental awareness. The presented scenarios help to identify the range of plausible development paths, thus building the basis for future model-based research. Highlights: Aviation scenarios for 2030 support decision-making in the face of uncertainty. Holistic system view based on pandemic-related, environmental, and societal factors. Pre-crisis traffic levels assumed to be reached in 2023 earliest and by 2026 latest. COVID-19 hygiene measures in place by at least 2024, some measures become permanent. In all scenarios, high environmental consciousness requires a sustainability push.